Mutational analysis of yeast mRNA capping enzyme. - Schwer, B (1994)
RNA guanylyltransferase (capping enzyme) catalyzes the transfer of GMP from GTP to the 5'-diphosphate end of mRNA. The capping reaction proceeds via an enzyme-guanylate intermediate in which GMP is linked covalently to a lysine residue of the enzyme. In the capping enzyme of Saccharomyces cerevisiae, GMP is attached to a 52-kDa polypeptide, identified as the product of the essential CEG1 gene. The amino acid sequence of the CEG1 protein includes a motif, Lys70-Thr-Asp-Gly, that is conserved at the active site of vaccinia virus RNA guanylyltransferase and which is similar to the KXDG sequence found at the active sites of RNA and DNA ligases. To evaluate the role of this motif in the function of the yeast enzyme, we have expressed the CEG1 protein in active form in Escherichia coli. Replacement of Lys70 or Gly73 with alanine abrogated enzyme-guanylate formation in vitro; in contrast, alanine substitutions at Thr71 or Asp72 merely reduced activity relative to wild-type enzyme. The K70A and G73A mutations were lethal to yeast, whereas yeast carrying the T71A and D72A alleles of CEG1 were viable. These results implicate Lys70 as the active site of yeast guanylyltransferase and provide evidence that cap formation per se is an essential function in eukaryotic cells.